2000
DOI: 10.1080/00140130050084879
|View full text |Cite
|
Sign up to set email alerts
|

Teamwork in multi-person systems: a review and analysis

Abstract: As the scope and complexity of modern task demands exceed the capability of individuals to perform, teams are emerging to shoulder the burgeoning requirements. Accordingly, researchers have striven to understand and enhance human performance in team settings. The purpose of this review is to summarize that research, from the theoretical underpinnings that drive it, to the identi® cation of team-level elements of success, to the methodologies and instruments that capture and measure those characteristics. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
142
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(147 citation statements)
references
References 59 publications
2
142
0
3
Order By: Relevance
“…Team members are expected not only to possess these KSAs, but often to perform them effectively in stressful situations (Cannon-Bowers & Salas, 1997;Volpe, Cannon-Bowers, Salas, & Spector, 1996), such as under time pressure, in distributed team environments, and facing information overload or deficiencies. Thus, as the use of teams in organizations increases and as the performance requirements of team members become progressively more complex, effective team training is becoming an organizational necessity (Paris, Salas, & Cannon-Bowers, 2000;Stout et al, 1997). Systematic and formal team training is expected to develop a team's ability to achieve high performance (Goldstein & Ford, 2002).…”
mentioning
confidence: 99%
“…Team members are expected not only to possess these KSAs, but often to perform them effectively in stressful situations (Cannon-Bowers & Salas, 1997;Volpe, Cannon-Bowers, Salas, & Spector, 1996), such as under time pressure, in distributed team environments, and facing information overload or deficiencies. Thus, as the use of teams in organizations increases and as the performance requirements of team members become progressively more complex, effective team training is becoming an organizational necessity (Paris, Salas, & Cannon-Bowers, 2000;Stout et al, 1997). Systematic and formal team training is expected to develop a team's ability to achieve high performance (Goldstein & Ford, 2002).…”
mentioning
confidence: 99%
“…14 Diversity with respect to age, educational level, status and non-industry work experience has been shown to result in higher turnover rates from teams, 14 yet a moderately diverse team is required to avoid mere replication of individual effort. 5 While, intuitively, team preselection to promote well-balanced teams appears preferable to naturally occurring groups, 16,17 this rarely occurs in the workplace. Health care teams, for example, are increasingly multidisciplinary in nature, and thus are associated with wide diversity with respect to gender, economic, political and ideological differences.…”
Section: Team Compositionmentioning
confidence: 99%
“…Paris et al [16] reviewed research in understanding human team performance and found no less than eight representative theories on teamwork. Such approaches examine, among other things, workrelated, interdependence, capability, lifecycle evolution or maturation, and task-oriented implications of the team member interactions or relationships.…”
Section: Related Workmentioning
confidence: 99%
“…While developing the agents and the model, we kept the following key topics in mind: implication of interdependence of team members [16]; agent communication; beliefs, desires, intentions [6]; what factors affect task performance [20]; technology used; how to share job or task models; and how the team interacts [15]. While some items were easily known (such as the task model: get all colors in the color sequence into the DropZone), we are most interested in how the team members interact.…”
Section: Approachmentioning
confidence: 99%